THE CONCEPT OF EDUCATION OF A CHILD IN A FAMILY IN THE WORK OF MICHEL MONTAIGN “EXPERIENCES” (Scientific journal of the Fergana State University, 2023)
In this article, we will focus on the content of the ideas of the French thinker Michel Montaigne, who lived and worked in the XVI century, in his work "Experiments" on the upbringing of children and the words he used in his work at that time. The development of family spirituality is based on the relationship between each member of the family as a person who has a certain spiritual world. The spiritual qualities of the father and mother in the family The Eastern traditions of the couple’s relationship determine the level of humanity and morality. It is important that the spiritual world of the family embodies such spiritual values ​​as mutual respect, appreciation, cooperation, tolerance, kindness, compassion, patience, humanity, nobility, respect for adults, respect for the little ones. As a result, the family is formed as a place of spirituality. Also, the third volume work "Experiments" by French thinker Michel Montaigne deals with the analysis of the views expressed on the upbringing of the child. The article collected samples based on comparative and paradigmatic methods. The examples given in this article also have an impact on the spiritual and patient upbringing of the younger generation.